Penyebab Rasa Malas Remaja di SMP Bani Abdillah Desa Cilebut, Kabupaten Bogor Tahun 2021: Causes of Laziness among Teenagers at Bani Abdillah Middle School, Cilebut Village, Bogor Regency in 2021 - Anastakim, Syavira; Sitorus, Giovaldo Gabe; Irayani, Salsa Putri (MPI Press, 2022)
Introduction: Since the COVID-19 pandemic entered Indonesia, all schools have implemented distance learning. Namely, the learning process that is reached using the internet. During this period of adjustment to the new learning process, many students have not been able to adapt. Some of them are lazy to study due to difficulty accessing learning, poor signal, lack of understanding of the material, lack of rest hours, and less conducive home environmental conditions. Objective: We conducted this research to find out what the main factors are for lazy students during the COVID-19 pandemic. Methods: This research method uses descriptive qualitative by filling out a questionnaire. Results: The results of this research show that students feel lazy due to lack of motivation, namely 89.3%. Therefore, we are holding a webinar to motivate students and provide solutions so that they don't feel lazy during the COVID-19 pandemic. Laziness is a habit that is learned and formed by environmental conditions and the people around it. Conclusion: Based on the results of the questionnaire, it was found that Bani Abdillah Middle School students felt lazy due to a lack of motivation or support from the surrounding environment. This motivation is very important to help the continuity of students' teaching and learning activities and to create a pleasant environment. Motivating students can be done by making a study agenda, determining a learning style, avoiding learning distractions, finding the right atmosphere, and studying with friends.